2023
DOI: 10.1021/acs.est.3c02857
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Fate, Human Exposure, and Toxicity of Commercial Photoinitiators

Xiaomeng Ji,
Jiefeng Liang,
Jiale Liu
et al.

Abstract: Photoinitiators (PIs) are a family of anthropogenic chemicals used in polymerization systems that generate active substances to initiate polymerization reactions under certain radiations. Although polymerization is considered a green method, its wide application in various commercial products, such as UV-curable inks, paints, and varnishes, has led to ubiquitous environmental issues caused by PIs. In this study, we present an overview of the current knowledge on the environmental occurrence, human exposure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 125 publications
0
5
0
Order By: Relevance
“…Synthetic antioxidants (AOs) are ubiquitous, high-productionvolume chemicals used as essential polymer additives in the manufacture of various industrial and consumer products to enhance product resistance to oxidative aging. 1 It has been reported that the global consumption of AOs is up to 700,000 tons per year for rubber manufacturing alone. 2 Generally, commercial synthetic AOs are divided according to their structures and functionalities into four categories: hindered phenol antioxidants (HPAs), aromatic amine antioxidants (AAs), organophosphite antioxidants (OPAs), and sulfurcontaining antioxidants (SAs).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic antioxidants (AOs) are ubiquitous, high-productionvolume chemicals used as essential polymer additives in the manufacture of various industrial and consumer products to enhance product resistance to oxidative aging. 1 It has been reported that the global consumption of AOs is up to 700,000 tons per year for rubber manufacturing alone. 2 Generally, commercial synthetic AOs are divided according to their structures and functionalities into four categories: hindered phenol antioxidants (HPAs), aromatic amine antioxidants (AAs), organophosphite antioxidants (OPAs), and sulfurcontaining antioxidants (SAs).…”
Section: ■ Introductionmentioning
confidence: 99%
“…6 Representative LMW HPAs include the well-known 2,6-di-tert-butyl-4-methylphenol (BHT) and 2,4di-tert-butyl-phenol (DBP). 1 In recent 20 years, to improve the performance of HPAs and slow their migration from products, a large number of BHT-derived MHPAs, represented by octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (AO 1076), have been introduced into the market. 8−10 To date, both LMW SPAs and MHPAs have been widely detected across multiple environmental media worldwide.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4,5,7−15 Commercial SAs are generally classified as aromatic amine antioxidants (AAs), sulfur-containing antioxidants (SAs), hindered phenolic antioxidants (HPAs), and organophosphate antioxidants (OPAs). 16,17 Among the various emerging SAs, amine antioxidants (AAs), containing aromatic amine groups based on anilines and structures with an aromatic ring and one or more amine groups, have recently attracted increasing attention. 7,15,18,19 AAs have been considered as new high-production volume (HPV) industrial chemicals, which include p-phenylenediamines (PPDs), diphenylamines (DPAs), naphthylamines (NPAs), and the DPG series of materials (e.g., 1,3diphenylguanidine (DPG), 1,2,3-triphenylguanidine (TPG), and 1,3-di-o-tolyguanidine (DTG)).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Significantly negative association with newborn birth weight and length was monitored for chlorpyrifos levels in umbilical cord plasma samples collected in New York City . Factually, humans are exposed to a cocktail of contaminants, and the relevant adverse outcomes usually originate from the complex chemical mixtures. , To our knowledge, systematic study on the Cl/Br-HOCs exposome in the early life stage and its exposure risks is still lacking.…”
Section: Introductionmentioning
confidence: 99%